(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Managers are critical part of a company’s success. Good managers lead others and have the skills and ability appropriate for their positions. Managers should be competent and keep up with change in all areas and use some methods of change. One of the areas is management. Ninety six electronics engineers of selected electronics industries were given survey in order to determine the level of competency of management skills. This study is beneficial for designing the training program necessary to enhance competency and overcome the attributed challenges. The result of the study revealed that electronics engineers are most competent in problem solving skill but least competent in conflict management skill. The major challenge encountered by electronics engineers is about managing and confronting an employee performance and the minor challenge is about management renewal.